DTX3L/ARTD9 contributes to inflammation of fibroblast-like synoviocytes by increasing STAT1 translocation. (June 2020) - Hong, Ruilong; Wang, Yuwu; Dong, Honghua; Geng, Rui
Highlights: This study investigated the role of DTX3L in TNF-induced inflammatory responses and analyzed the association between DTX3L and ARTD9. We examined the role of DTX3L and ARTD9 in cell invasiveness and inflammatory factors by overexpressing or inhibiting DTX3L and ARTD9 in FLS cells. Inhibit the expression of DTX3L and ARTD9, the production of MMP-9 and IL-6 were decreased. Furthermore, we found suppression of ARTD9 weakened the function of DTX3L-induced inflammation. When DTX3L was overexpressed, STAT1 could translocate into nucleus, and the nucleus expression of STAT1 was also increased under TNF-α stimulated. Inhibition of ARTD9 significantly decreased the DTX3L-induced cell invasion and cytokines secretion in FLS cells and the importation of STAT1 was weakened. Collectively our research proved DTX3L/ARTD9 may be a novel therapeutic target for RA. Abstract: Deltex-3-like (DTX3L), an E3 ligase, which is also known as B-lymphoma and BAL-associated protein (BBAP), is a member of the Deltex (DTX) family and was originally identified as a binding partner of diphtheria-toxin-like ADP-ribosyltransferase-9 (ARTD9). The present study found that DTX3L and ARTD9 were upregulated in synovial tissues obtained from rheumatoid arthritis (RA) patients compared with those from the controls. Healthy synovial tissues were obtained by arthroscopic biopsy from patients with meniscus injury (n = 10 samples) without a history of RA in the Orthopedic Department of the Affiliated Hospital of Nantong University. FLSs were isolated from RA patients who underwent total knee arthroplasty. We performed dual immunofluorescence staining on DTX3L and ARTD9, and these data strongly demonstrated that DTX3L and ARTD9 were colocalized with fibroblast-like synoviocytes (FLSs) in patients with RA. Furthermore, Western blot assays were performed to confirm that the expression levels of DTX3L and ARTD9 in the FLSs increased in a time-dependent manner and peaked at 24 h after TNF-α stimulation. Further, the inhibition of endogenous DTX3L and ARTD9 expression by RNA interference significantly suppressed the TNF-α-induced MMP-9 and IL-6 expression, as shown by Western blots. In contrast, overexpressing DTX3L and ARTD9 increased the MMP-9 and IL-6 mRNA levels in the TNF-α-stimulated FLSs. Moreover, DTX3L and ARTD9 associated with STAT1 under TNF-α-stimulated conditions to modulate STAT1 nuclear localization and transcriptional activity in an immunofluorescence staining assay. Collectively, our findings provide evidence that DTX3L and ARTD9 contribute to the production of inflammatory cytokines in FLSs from RA patients and may play a key role in the inflammatory process of RA via the STAT1 signal transduction pathway.